Board Gender Diversity and its Impact on Firm Risk-Taking - Hesniati, Hesniati; Vernando, Lovis; Haryanto, Hery; Arviano, Hengky (Department of Management, Faculty of Economics and Business, Universitas Negeri Semarang, 2024)
This study aims to analyze the gender diversity of boards of directors and its impact on firm risk-taking. It is interesting to study because the presence of women on the board of directors of a firm has garnered considerable attention in the last few years. The sample is drawn from the industrial sector listed on the Indonesian Stock Exchange from 2017 to 2021. Firm risk-taking is measured by the volatility of stock returns. Using panel data, the results of the research indicate that gender diversity has a significantly positive impact on firm risk-taking. This finding contributes that a female board of directors would lead to greater risk-taking than their male counterparts. This research provides a literature on gender diversity and firm risk-taking in a male-dominated sector in Indonesia, providing insights for investors and companies to consider the potential benefits of gender diversity on board of directors in managing firm risk-taking. Further research could apply other measurements of firm risk-taking and observe other male-dominated sectors for comparison to enhance the study’s limitation.